Pelatihan Ekonomi Rumah Tangga dan Manajemen Keuangan Keluarga Untuk Meningkatkan Kesejahteraan: Penelitian - Septi Wifasari; Yulistina; Fajar Budiyanto; Andi Urfia Awaliah; Dadang Purwo Ariwidodo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The training on household economics and family financial management aims to improve well-being. The program encompasses preparation, participant outreach and recruitment, training implementation, mentoring and monitoring, and program evaluation. The results indicate that the training on household economics and family financial management successfully improved participants' financial literacy, particularly in terms of knowledge, skills, and attitudes regarding financial management. Participants were able to prepare budgets, record cash flows, and plan savings and emergency funds. Furthermore, behavioral changes occurred, such as reduced consumer spending and wiser debt management. Positive impacts were seen in improved family well-being through more controlled spending, reduced reliance on loans, and increased family harmony. However, challenges such as unstable income, consumer habits, and lack of family support require continued mentoring to ensure the training's sustainability.